Hadis dalam Arus Budaya Global: Tantangan dan Respons Hadis terhadap Budaya Asing - Nazla Hayati Nufus; Salim Rosyadi; Adha Liandrini; Fahmi Andaluzi (El Nubuwwah Jurnal Studi Hadis, 2025)
This article examines foreign cultures from the perspective of the hadiths of the Prophet Muhammad (peace be upon him), focusing on how Muslims should respond to the challenges posed by foreign cultural influences that contradict the teachings of the Prophet. The discussion employs a thematic-analytical approach by inventorying and classifying relevant hadiths related to the research focus, which are then described and interpreted through textual and contextual analysis. Overall, this study finds that the Prophet (peace be upon him) issued strong warnings against inclinations toward or the imitation of foreign cultures that conflict with Islamic creed (Ê¿aqÄ«dah) and that may potentially undermine Islamic values, identity, and religious integrity. These hadiths emphasize the importance of avoiding the negative influences of traditions that often originate from outside the Islamic values. In responding to foreign cultural influences, Muslims are encouraged to adopt the hadiths of the Prophet (peace be upon him) as both a normative filter and a foundational guide for engaging with foreign cultures, so as to remain firmly committed to Islamic values, such as avoiding tashabbuh (imitation of non-Islamic practices), rejecting excessive materialism, maintaining ethical conduct, and preserving religious integrity. This study underscores the importance of safeguarding Islamic identity amid the currents of globalization that bring various deviant ideological and cultural influences. Nevertheless, Muslims may remain open to innovation without compromising Islamic values. This research contributes to the enrichment of thematic hadith studies, particularly in the context of the relationship between Islam and global culture, and reaffirms the role of hadith as a normative guide in shaping Muslim religious attitudes in the face of the complexities of modern cultural challenges.